In-situ alkali-reducing film-forming pre-lithiation silicon monoxide-based composite material, preparation method thereof, negative electrode and lithium-containing battery
By using in-situ alkali-reducing film-forming prelithiated silicon oxide composite materials in lithium-ion batteries, and using dopamine hydrochloride to form a carbon coated film, the problems of low first-time charging efficiency and insufficient circulation performance of silicon oxygen materials are solved. Improves the stability and efficiency of the battery, and achieves simplification of the process and reduction of costs.
Patent Information
- Application Number
- CN202310722546.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
AI Technical Summary
Among the existing lithium-ion batteries, the first charging efficiency of silicon oxygen materials is low and the circulation performance is limited. The existing pre-lithiation process has a high operating environment and high safety risks, making it difficult to achieve industrial promotion.
In situ alkali-reduced film-forming prelithiated silicon oxide composite material is used to form a carbon coated film through in-situ reaction of dopamine hydrochloride, reducing the volume expansion and alkalinity of lithium elements, and improving the first-time Coulomb efficiency and cycle stability.
The first Coulomb efficiency and cycle stability of the oxidized subunit negative electrode material in lithium-ion batteries have been improved, and the process is simple, easy to operate, low cost, and easy to scale.
Smart Images

Figure CN119153639A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of lithium-ion battery materials, and in particular, to an in-situ alkali reduction film-forming pre-lithiated silicon oxide-based composite material and a preparation method thereof, a negative electrode and a lithium-containing battery. Background Art
[0002] Lithium-ion batteries have been widely used in portable electronic products and electric vehicles due to their high operating voltage, long cycle life, no memory effect, low self-discharge, and environmental friendliness. At present, commercial lithium-ion batteries mainly use graphite-based negative electrode materials, but their theoretical specific capacity is only 372mAh / g, which cannot meet the high energy density requirements of lithium-ion batteries. Although the existing Si has a theoretical capacity of up to 4200mAh / g, its expansion is up to 300%, which affects the cycle performance and restricts market promotion and application. The corresponding silicon-oxygen material has better cycle performance, but the first efficiency is low. During the first charge, 20-50% of the lithium is consumed for SEI film formation, which greatly reduces the first coulomb efficiency. As the first efficiency of the positive electrode material becomes higher and higher, it is particularly important to improve the first efficiency of silicon-oxygen materials.
[0003] At present, an effective way to improve the first effect of silicon oxide materials is to pre-dope them with lithium so that the irreversible lithium consumption phase in the silicon oxide material can be reacted in advance. The existing industrial method is to directly coat a lithium layer on the surface of the pole piece to achieve the effect of reducing the lithium consumption of the positive electrode. However, this method has high requirements for the operating environment and has great safety hazards, so it is difficult to achieve industrial promotion. The problem of poor processing performance is generally encountered in the process of pre-lithium on the material side to obtain the first effect improvement. This is mainly because the lithium on the surface of the material makes the material itself unstable and difficult to preserve, and it is easy to cause the pH value of the slurry to increase during the slurrying process when it is used, and react with the binder and / or solvent water to produce gas, which is difficult to slurry, but causes the battery performance to deteriorate. Therefore, optimizing the structure and preparation process conditions of the powder pre-supplemented with lithium and forming a preparation method compatible with the existing battery system is the key to improving the electrochemical performance of silicon-based negative electrode materials. Summary of the invention
[0004] The purpose of the present disclosure is to provide an in-situ alkali reduction film-forming pre-lithiated silicon oxide-based composite material and its preparation method, negative electrode and lithium-containing battery, which can form a carbon coating film on the surface of lithium-containing silicon oxide through the in-situ reaction of dopamine hydrochloride to avoid gas production in the slurry; it can also reduce the volume expansion of the negative electrode material, improve the first coulomb efficiency and cycle stability.
[0005] In order to achieve the above-mentioned objectives, the first aspect of the present disclosure provides an in-situ alkali reduction film-forming pre-lithiated silicon oxide-based composite material, wherein the pre-lithiated silicon oxide-based composite material comprises a core-shell structure having a core and an outer shell; wherein the core comprises silicon oxide and a lithium element component, and the lithium element component is selected from one or two of lithium silicates and silicon-lithium alloys; the surface of the core has a carbon coating film formed as the outer shell; the carbon coating film is obtained by an in-situ reaction of dopamine hydrochloride on the surface of the core.
[0006] Optionally, the content of the lithium element component in the pre-lithiated silicon oxide-based composite material is 0.01 to 50% by weight, preferably 0.1 to 10% by weight, based on the total amount of lithium element; optionally, the lithium element component also includes metallic lithium;
[0007] Optionally, the content of the shell is 5 to 50% by weight, preferably 5 to 30% by weight, based on the total weight of the pre-lithiated silicon oxide-based composite material;
[0008] Preferably, a solid dispersant intermediate layer is further included between the inner core and the outer shell of the pre-lithiated silicon oxide-based composite material.
[0009] Optionally, the average particle size of the pre-lithiated silicon oxide-based composite material is 0.5 to 50 μm, and the BET specific surface area is 0.1 to 100 m 2 / g, total pore volume is 0.001~0.5cm 3 / g;
[0010] Optionally, the shell has a thickness of 0.01 to 1 μm, preferably 0.01 to 0.5 μm.
[0011] The second aspect of the present disclosure provides a method for preparing an in-situ alkali reduction film-forming pre-lithiated silicon oxide-based composite material, comprising the following steps: S1, contacting metallic lithium with silicon oxide powder and performing solid phase homogenization treatment to obtain a first product; S2, contacting the first product with a solid dispersant and performing a homogenization dispersion treatment to obtain a second product; S3, contacting the second product with alkali reduction reaction raw materials and a solvent and performing a mixing homogenization treatment to obtain a mixed slurry; S4, spray granulating the mixed slurry to obtain a third product; S5, performing a thermal stabilization treatment on the third product; wherein the above steps S1 to S5 are performed in an inert atmosphere.
[0012] Optionally, in step S1, the weight ratio of the metallic lithium to the silicon dioxide powder is 1:1 to 100, preferably 1:5 to 50;
[0013] Optionally, the metallic lithium is selected from one or more of lithium ingots, lithium wires, lithium powders and lithium sheets;
[0014] Optionally, the average particle size of the silicon oxide powder is 0.1 to 10 μm, and the BET specific surface area is 0.1 to 100 m 2 / g.
[0015] Optionally, in step S1, the solid phase homogenization treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser;
[0016] Optionally, the conditions for the solid phase homogenization treatment include: a ball milling speed of 300 to 2000 r / min, a ball milling time of 6 to 72 h, and a ball-to-material ratio of 1 to 20:1; preferably, the ball milling speed is 500 to 1000 r / min, the ball milling time is 12 to 24 h, and the ball-to-material ratio is 10 to 20:1.
[0017] Optionally, in step S2, the weight ratio of the solid dispersant to the metallic lithium is 1 to 50:1, preferably 5 to 10:1;
[0018] Optionally, the solid dispersant is selected from one or more of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon and soft carbon.
[0019] Optionally, in step S2, the homogenization and dispersion treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser;
[0020] Optionally, the conditions for the homogeneous dispersion treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 12 h, and a ball-to-material ratio of 1 to 20:1; preferably, a ball milling speed of 100 to 300 r / min, a ball milling time of 5 to 8 h, and a ball-to-material ratio of 10 to 20:1.
[0021] Optionally, in step S3, the weight ratio of the alkali reduction reaction raw material to the metallic lithium is 1 to 50:1, preferably 10 to 30:1; the weight ratio of the solvent to the alkali reduction reaction raw material is 10 to 100:1, preferably 50 to 100:1;
[0022] Optionally, the solid content of the mixed slurry is 1 to 30% by weight, preferably 5 to 20% by weight;
[0023] Preferably, the raw materials for the alkalinity reduction reaction include dopamine hydrochloride and an optional organic acid; optionally, the organic acid is selected from one or more of oxalic acid, malic acid and citric acid;
[0024] Optionally, the solvent is selected from one or more of ethanol, isopropanol, n-butanol, cyclohexane and cyclohexanone.
[0025] Optionally, in step S3, the mixing and homogenizing treatment comprises mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser;
[0026] Optionally, the conditions for the mixing homogenization treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 24 h, and a ball-to-material ratio of 1 to 20:1; preferably, a ball milling speed of 100 to 300 r / min, a ball milling time of 0.5 to 3 h, and a ball-to-material ratio of 10 to 20:1.
[0027] Optionally, in step S4, the conditions of the spray granulation treatment include: an inlet temperature of 100 to 300° C., an outlet temperature of 50 to 200° C., a carrier gas flow rate of 10 to 100 L / min, and a pressure of -0.10 to -0.05 MPa;
[0028] Preferably, the inlet temperature is 120 to 240°C, the outlet temperature is 80 to 150°C, the carrier gas flow rate is 30 to 60 L / min, and the pressure is -0.10 to -0.08 MPa;
[0029] The carrier gas is selected from one or more of argon, nitrogen and helium;
[0030] Preferably, the average particle size of the third product obtained by spray granulation is 5 to 50 μm.
[0031] Optionally, in step S5, the thermal stabilization treatment includes a multi-stage sintering treatment;
[0032] Preferably, the thermal stabilization treatment includes a first sintering treatment and a second sintering treatment performed sequentially; wherein the conditions of the first sintering treatment include: heating to 200-500°C at a heating rate of 1-3°C / min, and then maintaining the temperature for 1-6 hours; the conditions of the second sintering treatment include: heating to 600-1200°C at a heating rate of 2-5°C / min, and then maintaining the temperature for 1-12 hours;
[0033] Preferably, the conditions for the first sintering treatment include: heating to 250-400°C at a heating rate of 1-2°C / min, and then maintaining the temperature for 2-3 hours; the conditions for the second sintering treatment include: heating to 700-900°C at a heating rate of 3-5°C / min, and then maintaining the temperature for 2-6 hours.
[0034] A third aspect of the present disclosure provides an in-situ alkali reduction film-forming pre-lithiated silicon oxide-based composite material prepared by the method described in the second aspect of the present disclosure.
[0035] A fourth aspect of the present disclosure provides a negative electrode for a lithium-containing battery, which comprises the in-situ alkali reduction film-forming pre-lithiated silicon oxide-based composite material described in the first aspect or the third aspect of the present disclosure.
[0036] A fifth aspect of the present disclosure provides a lithium-containing battery, which includes the negative electrode described in the fourth aspect of the present disclosure.
[0037] Through the above technical scheme, the present disclosure provides an in-situ alkali reduction film pre-lithiation silicon oxide-based composite material and its preparation method, negative electrode and lithium-containing battery. The present disclosure provides a pre-lithiation silicon oxide-based composite material with a core-shell structure, wherein the core has lithium silicate and / or silicon-lithium alloy to achieve pre-lithiation; silicon oxide with low specific capacity is used as a matrix to reduce the volume expansion phenomenon in the use of negative electrode materials; and dopamine hydrochloride is used on the surface of the core through an in-situ reaction to obtain a carbon coating film as a shell, reducing the alkalinity of the pre-lithiation material while in-situ constructing a dense and stable carbon coating film structure, avoiding direct contact between components in the core such as lithium salt, silicon-lithium alloy, and lithium and the outside world, and in the process of homogenization, the slurry pH will not increase, the slurry remains neutral, and the slurry gas production is suppressed; the in-situ alkali reduction film pre-lithiation silicon oxide-based composite material provided by the present disclosure can improve the first coulomb efficiency and cycle stability of the oxide negative electrode material in the application of battery negative electrode materials. And it has the characteristics of controllable lithium content, simple process, simple operation, environmentally friendly process, low cost and easy scale. It is also compatible with the existing negative electrode material system of lithium-ion batteries and can be directly applied to the existing negative electrode material system of lithium-ion batteries.
[0038] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0040] Figure 1 is an exemplary structural diagram of a pre-lithiation negative electrode material provided by the present disclosure;
[0041] Figure 2 is a scanning electron microscope photograph of the pre-lithiation negative electrode material prepared in Example 1 of the present disclosure;
[0042] Figure 3 is a transmission electron microscope photograph of the pre-lithiation negative electrode material prepared in Example 1 of the present disclosure;
[0043] Figure 4 is a high-magnification transmission electron microscope photograph of the pre-lithiation negative electrode material prepared in Example 1 of the present disclosure;
[0044] Figure 5 is an X-ray diffraction pattern of the pre-lithiation negative electrode material prepared in Example 1 of the present disclosure;
[0045] Figure 6 is the Li 1s X-ray photoelectron high-resolution scanning energy spectrum of the pre-lithiation negative electrode material prepared in Example 1 of the present disclosure;
[0046] Figure 7 is the Li 1s X-ray photoelectron high-resolution scanning spectrum of the intermediate product prepared in Example 1 of the present disclosure;
[0047] Figure 8 is a first charge and discharge curve diagram of the pre-lithiation negative electrode material prepared in Example 1 of the present disclosure at a current density of 0.2C;
[0048] Fig. 9 This is a cycle performance diagram of the pre-lithiation negative electrode material prepared in Example 1 of the present disclosure at a current density of 0.2C. DETAILED DESCRIPTION
[0049] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0050] The first aspect of the present disclosure provides an in-situ alkali reduction film-forming pre-lithiated silicon oxide-based composite material, wherein the pre-lithiated silicon oxide-based composite material comprises a core-shell structure having a core and an outer shell;
[0051] The inner core comprises silicon monoxide and lithium components, wherein the lithium component is selected from one or two of lithium silicates and silicon-lithium alloys; the surface of the inner core has a carbon coating film to form the outer shell; the carbon coating film is obtained by in-situ reaction of dopamine hydrochloride on the surface of the inner core.
[0052] The present disclosure provides an in-situ alkali reduction film pre-lithiation silicon oxide-based composite material, which has a core-shell structure, wherein the core has lithium silicate and / or silicon-lithium alloy, and pre-supplementation of lithium is achieved; silicon oxide with low specific capacity is used as a matrix, and the volume expansion phenomenon in the use of negative electrode materials is reduced; and dopamine hydrochloride is used on the surface of the core through an in-situ reaction to obtain a carbon coating film as a shell, which reduces the alkalinity of the pre-lithiation material and constructs a dense and stable carbon coating film structure in situ, avoiding direct contact between components in the core such as lithium salt, silicon-lithium alloy, and lithium and the outside world. During the homogenization process, the slurry pH does not increase, the slurry remains neutral, and the slurry gas production is suppressed; the in-situ alkali reduction film pre-lithiation silicon oxide-based composite material provided by the present disclosure can improve the first coulomb efficiency and cycle stability of the oxide negative electrode material in the application of battery negative electrode materials. And it has the characteristics of controllable lithium content, simple process, simple operation, environmentally friendly process, low cost, and easy scale. It is also compatible with the existing negative electrode material system of lithium-ion batteries and can be directly applied to the existing negative electrode material system of lithium-ion batteries.
[0053] In the present disclosure, the general chemical formula of lithium silicate in the core is LiSi x O y Schematically represented, wherein 0<x≤10, 0<y≤10. The values of x and y are determined by XRD.
[0054] In one embodiment, the pre-lithiated silicon oxide-based composite material further includes an intermediate layer between the inner core and the outer shell; the intermediate layer is obtained from a carbonizable solid dispersant.
[0055] In the present disclosure, the middle layer of the pre-lithiated silicon oxide-based composite material may be composed of amorphous carbon, and the outer shell is composed of a carbon coating layer with higher crystallinity, and the carbon in the middle layer and the outer shell exists in different forms.
[0056] In a preferred embodiment, the density of the outer shell is greater than the density of the middle layer.
[0057] In a preferred embodiment, in the transmission electron microscope photograph of the pre-lithiated silicon oxide-based composite material, there is a contrast between the middle layer and the outer shell; in the transmission electron microscope photograph, the brightness of the middle layer is significantly higher than that of the outer shell.
[0058] In a specific embodiment, the solid dispersant is selected from one or more of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon and soft carbon.
[0059] In one embodiment, the content of the lithium component in the pre-lithiated silicon oxide-based composite material particles is 0.01 to 50% by weight, preferably 0.1 to 10% by weight, based on the total amount of lithium. The total content of lithium in the present disclosure can be calculated according to the amount of raw materials added during the preparation process.
[0060] In one embodiment, the lithium element component further comprises metallic lithium, which comes from unreacted metallic lithium.
[0061] In one embodiment, a solid dispersant intermediate layer is further included between the inner core and the outer shell of the pre-lithiated silicon oxide-based composite material.
[0062] In one embodiment, the content of the shell is 5 to 50% by weight, preferably 5 to 30% by weight, based on the total weight of the pre-lithiated silicon oxide-based composite material particles. The content of the shell in the present disclosure can be calculated according to the amount of raw materials added during the preparation process.
[0063] In a specific embodiment, the thickness of the shell is 0.01 to 1 μm, preferably 0.01 to 0.5 μm. The thickness of the shell in the present disclosure can be measured by a transmission electron microscope photograph of the negative electrode material.
[0064] In one embodiment, the pre-lithiated silicon oxide-based composite material has an average particle size of 0.5 to 50 μm, an average pore size of 1 to 30 nm, and a BET specific surface area of 0.1 to 100 m 2 / g, total pore volume is 0.001~0.5cm 3 / g; Preferably, the average particle size of the pre-lithiated silicon oxide-based composite material is 5 to 30 μm, the average pore size is 5 to 20 nm, and the BET specific surface area is 1 to 20 m 2 / g, total pore volume is 0.005~0.05cm 3 / g.
[0065] A second aspect of the present disclosure provides a method for preparing an in-situ alkali reduction film-forming pre-lithiated silicon oxide-based composite material, comprising the following steps:
[0066] S1, contacting metallic lithium with silicon oxide powder and performing solid phase homogenization to obtain a first product;
[0067] S2, contacting the first product with a solid dispersant and performing a homogeneous dispersion treatment to obtain a second product;
[0068] S3, contacting the second product with a raw material for alkali reduction reaction and a solvent and performing a mixing and homogenization treatment to obtain a mixed slurry;
[0069] S4, spray granulating the mixed slurry to obtain a third product;
[0070] S5, performing heat stabilization treatment on the third product;
[0071] The above steps S1 to S5 are carried out in an inert atmosphere.
[0072] The present invention provides a method for preparing a pre-lithiation negative electrode material, which uses silicon oxide and metallic lithium as raw materials, realizes the introduction of lithium through solid phase homogenization treatment, adopts silicon oxide with low specific capacity as a matrix, reduces the volume expansion phenomenon of the negative electrode material in use; and by adding a solid dispersant for dispersion and homogenization, it is possible to avoid the adhesion and agglomeration of silicon oxide and lithium during the reaction, so that the silicon oxide-lithium particles are fully dispersed; at the same time, the dispersant can also form a dispersed conductive network, increase the conductivity of the particles, and inhibit the decrease in conductivity caused by the introduction of lithium; the present invention mixes and homogenizes the second product obtained by the homogenization dispersion treatment with the alkali reduction reaction raw material, during which the alkaline lithium element on the surface of the second product reacts with the alkali reduction reaction raw material to form an alkali reduction film-forming reaction to form a carbonizable carbon coating film, thereby reducing the alkalinity of the pre-lithiation material and constructing a dense and stable carbon coating film structure in situ, avoiding direct contact of the lithium element component with the outside world. During the homogenization process, the pH of the slurry will not increase, the slurry remains neutral, and the gas production of the slurry is suppressed; in-situ alkali reduction film formation requires an alkaline environment. The introduction of metallic lithium in the preparation process of the present invention will make the reaction system alkaline, providing an alkaline environment for the in-situ reaction film formation of the alkali reduction reaction raw materials, and there is no need to additionally adjust the reaction system to be alkaline, and the alkalinity of the reaction system is reduced through the in-situ alkali reduction film formation reaction of the alkali reduction reaction raw materials; and the present invention sprays and granulates the mixed slurry containing the second product and the alkali reduction reaction raw materials, which can make the slurry dry and form quickly, and the coating effect is more uniform and dense; finally, through thermal stabilization treatment, the introduced lithium element is continuously diffused into the silicon oxide, reacts with the silicon oxide, and forms a thermodynamically relatively stable lithium silicate to achieve pre-lithiation, while suppressing the growth of silicon grains inside the silicon oxide particles, thereby improving the first coulombic efficiency and cycle stability of the silicon oxide negative electrode material.
[0073] In a specific embodiment, the inert atmosphere comprises one or more of nitrogen, helium, neon, argon, krypton and xenon; the water content of the inert atmosphere is less than 0.1 wt%, and the oxygen content is less than 0.1 wt%.
[0074] In one embodiment, in step S1, the weight ratio of the metal lithium to the silicon dioxide powder is 1:1 to 100, preferably 1:5 to 50. The preferred weight ratio of the metal lithium to the silicon dioxide powder provided by the present disclosure is used for the preparation reaction, which can further control the content of the lithium element in the negative electrode material and further improve the initial coulombic efficiency and cycle stability.
[0075] In a specific embodiment, the metallic lithium is selected from one or more of lithium ingots, lithium wires, lithium powders and lithium sheets.
[0076] In a specific embodiment, the average particle size of the silicon oxide powder is 0.1 to 10 μm, and the BET specific surface area is 0.1 to 100 m 2 / g; preferably, the average particle size of the silicon oxide powder is 0.5-5 μm and the BET specific surface area is 0.1-20 m 2 / gThe silicon dioxide powder used in the present invention can be purchased through conventional channels or prepared by known methods.
[0077] In one embodiment, in step S1, the solid phase homogenization treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser. The device used in the present disclosure is a device of conventional structure in the art.
[0078] In one embodiment, the conditions of the solid phase homogenization treatment include: a ball milling speed of 300 to 2000 r / min, a ball milling time of 6 to 72 hours, and a ball-to-material ratio of (1 to 20): 1. In the solid homogenization reaction treatment process, the particle size of the silicon oxide matrix and the metallic lithium is reduced, and part of the metallic lithium enters the pores of the silicon oxide matrix, and lithium elements are introduced into the inner core to form lithium silicate in the inner core. As the charge and discharge process proceeds, the lithium elements pre-embedded in the silicon oxide are continuously released to supplement the consumption and loss of lithium ions during the battery cycle, thereby improving the stability of the battery negative electrode.
[0079] In a preferred embodiment, the solid phase homogenization treatment conditions include: ball milling speed of 500-1000 r / min, ball milling time of 12-24 h, and ball to material ratio of (10-20): 1. The solid phase homogenization treatment according to the process conditions of this embodiment can further improve the performance of the negative electrode material.
[0080] In one embodiment, in step S2, the weight ratio of the solid dispersant to metallic lithium is 1 to 50:1, preferably 5 to 10:1.
[0081] In a specific embodiment, the solid dispersant is selected from one or more of natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon and soft carbon. The solid dispersant used in the present disclosure is easy to obtain and has good compatibility with the battery negative electrode system.
[0082] In one embodiment, in step S2, the homogenizing and dispersing treatment comprises mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser.
[0083] In one embodiment, the conditions for the homogenous dispersion treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 12 h, and a ball to material ratio of (1 to 20):1.
[0084] In a preferred embodiment, the conditions for the homogenous dispersion treatment include: a ball milling speed of 100 to 300 r / min, a ball milling time of 5 to 8 h, and a ball to material ratio of (10 to 20):1.
[0085] In one embodiment, in step S3, the weight ratio of the alkali reduction reaction raw material to the metallic lithium is 1 to 50:1, preferably 10 to 30:1; the weight ratio of the solvent to the alkali reduction reaction raw material is 10 to 100:1, preferably 50 to 100:1;
[0086] Optionally, the solid content of the mixed slurry is 1 to 30% by weight, preferably 5 to 20% by weight. The solid content of the mixed slurry is calculated by the amount of solvent added during the preparation process.
[0087] In one embodiment, the raw materials for the alkalinity reduction reaction include dopamine hydrochloride and an optional organic acid; the organic acid is selected from one or more of oxalic acid, malic acid and citric acid;
[0088] Optionally, the solvent is selected from one or more of ethanol, isopropanol, n-butanol, cyclohexane and cyclohexanone.
[0089] According to the present disclosure, taking dopamine hydrochloride as an example, the reaction formula for the in-situ film-forming reaction between dopamine hydrochloride and alkaline lithium on the surface of the material is as follows:
[0090] 8H 11 NO2·H + +OH - →C8H 11 NO2+H2O. The organic polymer formed by the reaction can be carbonized in the subsequent thermal stabilization treatment to form a dense carbon coating surface.
[0091] In one embodiment, in step S3, the mixing and homogenizing treatment comprises mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser.
[0092] In one embodiment, the conditions for the mixing and homogenizing treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 24 h, and a ball to material ratio of (1 to 20): 1. In a preferred embodiment, the conditions for the mixing and homogenizing treatment include: a ball milling speed of 100 to 300 r / min, a ball milling time of 0.5 to 3 h, and a ball to material ratio of (10 to 20): 1. The present invention discloses that an in-situ alkali reduction reaction occurs during the mixing and homogenizing treatment, which is simple to operate and has a uniform reaction.
[0093] In one embodiment, in step S4, the conditions of the spray granulation treatment include: an inlet temperature of 100 to 300°C, an outlet temperature of 50 to 200°C, a carrier gas flow rate of 10 to 100 L / min, and a pressure of -0.1 to -0.05 MPa; the carrier gas is selected from one or more of argon, nitrogen and helium gases.
[0094] In a preferred embodiment, in step S4, the conditions of the spray granulation treatment include: an inlet temperature of 120 to 240°C, an outlet temperature of 80 to 150°C, a carrier gas flow rate of 30 to 60 L / min, and a pressure of -0.1 to -0.08 MPa.
[0095] The present invention adopts the mixed slurry for spray granulation, which is beneficial to improve the coating uniformity and avoid the damage to the particle pore structure. The present invention can adopt the conventional spray granulation device in the art for spray granulation.
[0096] In a specific embodiment, the average particle size of the third product obtained by spray granulation can be 5 to 50 μm.
[0097] In one embodiment, the thermal stabilization treatment includes a multi-stage sintering treatment;
[0098] Preferably, the thermal stabilization treatment includes a first sintering treatment and a second sintering treatment performed sequentially; wherein the conditions of the first sintering treatment include: heating to 200-500°C at a heating rate of 1-3°C / min, and then maintaining the temperature for 1-6 hours; the conditions of the second sintering treatment include: heating to 600-1200°C at a heating rate of 2-5°C / min, and then maintaining the temperature for 1-12 hours.
[0099] In a preferred embodiment, the conditions of the first sintering treatment include: heating to 250-400°C at a heating rate of 1-2°C / min, and then maintaining the temperature for 2-3 hours; the conditions of the second sintering treatment include: heating to 700-900°C at a heating rate of 3-5°C / min, and then maintaining the temperature for 2-6 hours.
[0100] By performing thermal stabilization through staged temperature rise sintering and limiting the thermal stabilization temperature within the above range, the growth of silicon grains inside the silicon particles can be further suppressed, and the decrease in cycle stability can be further prevented; it also helps the lithium element to migrate into the silicon oxide core and react with silicon oxide to form lithium silicate.
[0101] A third aspect of the present disclosure provides an in-situ alkali reduction film-forming pre-lithiated silicon oxide-based composite material prepared by the method described in the second aspect of the present disclosure.
[0102] A fourth aspect of the present disclosure provides a negative electrode for a lithium-containing battery, which comprises the in-situ alkali reduction film-forming pre-lithiated silicon oxide-based composite material described in the first aspect or the third aspect of the present disclosure.
[0103] According to the present disclosure, the negative electrode can be prepared by a method known in the art. For example, the negative electrode is obtained by slurry coating, and the slurry includes the pre-lithiation negative electrode material provided by the present disclosure, a conductive agent, a binder, etc., and the conductive agent, the binder, etc. are conventionally selected in the art.
[0104] A fifth aspect of the present disclosure provides a lithium-containing battery, which includes the negative electrode described in the fourth aspect of the present disclosure.
[0105] The pre-lithiation negative electrode material provided by the present disclosure can be directly applied to the existing lithium-containing battery system, and can also be used in combination with lithium-ion battery graphite negative electrode materials, silicon-carbon negative electrode materials, silicon oxide negative electrode materials, etc. When the prepared high-stability pre-lithiation silicon oxide-based negative electrode material is applied to lithium-ion batteries, the first coulombic efficiency and cycle stability of lithium-ion batteries are significantly improved.
[0106] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.
[0107] In the following examples, unless otherwise specified, the raw materials used are commercially available products.
[0108] In the following examples, the specific testing methods are as follows:
[0109] The average particle size was measured using an optical particle size analyzer, the instrument model being Mastersizer 3000;
[0110] The SEM test method is scanning electron microscope, and the instrument model is S4800 of Hitachi, Japan;
[0111] The XRD test method is an X-ray diffractometer, and the instrument model is the X'Pert PRO powder X-ray diffractometer from PANalytical;
[0112] The XPS test method is X-ray photoelectron spectrometer, and the instrument model is VG ESCALAB;
[0113] The test method for electrochemical cycle performance is the blue electric test system, and the instrument model is CT3001A.
[0114] The spray granulation device was BUCHI Mini Spray Dryer B-290.
[0115] Dopamine hydrochloride was purchased from Sinopharm.
[0116] Example 1
[0117] In an inert environment without water or oxygen, 2g of silicon dioxide powder and 0.02g of lithium metal ingot were weighed and placed in a zirconium oxide ball mill (the weight ratio of lithium metal to silicon dioxide powder was 1:100), and then sealed and transferred to a planetary ball mill for ball milling. The ball-to-material ratio of the ball milling was 20:1, the diameters of the zirconium balls were 5.5mm, 3.0mm, and 2.0mm, and the ratio was 2:5:3. The ball milling speed was 500 rpm and the ball milling time was 12 hours. Then 0.1g of natural graphite was added to continue the ball milling (the weight ratio of the solid dispersant to lithium metal was 5:1), the ball milling speed was 450 rpm, and the ball milling time was 2 hours. 0.5 g of dopamine hydrochloride (the weight ratio of dopamine hydrochloride to metal lithium is 25:1) and 30 g of solvent cyclohexane (the weight ratio of solvent to dopamine hydrochloride is 60:1) were added, the ball milling speed was 450 rpm, the ball milling time was 2 hours, and a mixed slurry was obtained, and the solid content in the mixed slurry was 8.7% by weight. The mixed slurry was spray granulated, the inlet temperature was 180°C, the outlet temperature was 90°C, Ar gas was used as carrier gas, the carrier gas flow rate was 30L / min, and the pressure was -0.08MPa, to obtain a lithium-containing silicon oxide-based composite material precursor, and the average particle size of the spray granulation product was 15.3μm. The lithium-containing silicon oxide material precursor was placed in a tube furnace under an argon atmosphere for thermal stabilization and two-stage sintering: first, the temperature was raised to 300°C at a rate of 2°C / min, then kept constant for 2 hours, and after preheating and stabilization, the temperature was raised to 900°C at a rate of 5°C / min, and then kept constant for 2 hours. After cooling to room temperature, the pre-lithiated silicon oxide-based composite material was obtained, which was recorded as C-1.
[0118] The scanning electron microscope image of the pre-lithiated silicon oxide-based composite material C-1 is shown in Figure 2 As shown, the transmission electron microscope photo of C-1 is as follows Figure 3 As shown by Figure 3 It can be seen that C-1 has a dense and complete carbon coating layer on the outermost side (the darker part in the figure, as indicated by the arrow in the figure), and the thickness of the outer carbon coating layer is about 10 to 30 nm. Between the carbon coating film and the inner core, there is an amorphous coating layer with lower density formed by ball milling of solid dispersant natural graphite (the lighter part in the figure, as indicated by the arrow in the figure).
[0119] High-magnification transmission electron microscopy photos of pre-lithiated silicon oxide-based composite material C-1 are shown in Figure 4 The X-ray diffraction pattern is shown in Figure 5 As shown, it can be seen that the pre-lithiation material prepared in this embodiment contains Li2Si2O5 lithium silicate and lithium silicon alloy.
[0120] The Li 1s X-ray photoelectron high-resolution scanning energy spectrum of the pre-lithiated silicon oxide-based composite material C-1 is shown in Figure 6As shown, it can be seen that there is no characteristic peak of Li in the figure; the Li 1s X-ray photoelectron high-resolution scanning spectrum of the intermediate product after adding natural graphite solid dispersant for ball milling in this embodiment is as follows Figure 7 As shown in the figure, a sharp characteristic peak of Li appears. Figure 6 and Figure 7 By comparison, it can be seen that the method provided by the present invention undergoes in-situ alkali reduction and film formation during the preparation process, and the surface of the material does not contain lithium.
[0121] The electrochemical capacity-voltage test results of lithium-ion batteries assembled from pre-lithiated silicon oxide-based composite materials C-1 are shown in Figure 8 As shown, the current density is 0.2C, the first charge capacity is 835.1mAh / g, the first discharge capacity is 980.2mAh / g, and the first coulombic efficiency is 85.2%, indicating that the first charge capacity and the first coulombic efficiency of the battery are high; the relationship between the capacity retention rate of the battery and the number of cycles is shown in Fig. 9 As shown, it can be seen that as the charge and discharge cycle proceeds, the pre-embedded lithium plays a role. After 250 cycles, the capacity retention rate is still above 120%, showing excellent cycle performance.
[0122] Comparative Example 1
[0123] Compared with Example 1, this comparative example only performs a carbon coating by sintering a solid dispersant, and does not perform in-situ alkalinity reduction film formation of dopamine hydrochloride, and specifically comprises the following steps:
[0124] In an inert environment without water and oxygen, 2g of silicon dioxide powder and 0.02g of metal lithium ingot (the weight ratio of metal lithium to silicon dioxide powder is 1:100) are weighed and placed in a zirconium oxide ball milling jar, which is sealed and transferred to a planetary ball mill for ball milling. The ball-to-material ratio of the ball milling is 20:1, the diameters of the zirconium balls are 5.5mm, 3.0mm, and 2.0mm, respectively, and the ratio is 2:5:3. The ball milling speed is 500 rpm, and the ball milling time is 12 hours. Then 0.1g of natural graphite (the weight ratio of solid dispersant to metal lithium is 5:1) is added to continue ball milling, the ball milling speed is 450 rpm, and the ball milling time is 2 hours. Then it is placed in a tubular furnace under an argon atmosphere for thermal stabilization and two-stage sintering treatment: first, the temperature is raised to 300℃ at a rate of 2℃ / min, and then the temperature is kept constant for 2h, and preheating and stabilization is performed; then the temperature is raised to 900℃ at a heating rate of 5℃ / min, and then the temperature is kept constant for 2h. After cooling to room temperature, the material was discharged to obtain a pre-lithiated silicon 2 oxide negative electrode material, which was recorded as D-1.
[0125] Comparative Example 2
[0126] The difference between this comparative example and Example 1 is that metallic lithium is replaced by lithium carbonate of equal mass as the lithium source; the rest of the process is the same as Example 1, and a pre-lithiated silicon 2 oxide negative electrode material is obtained, which is recorded as D-2.
[0127] Comparative Example 3
[0128] The difference between this comparative example and Example 1 is that only one carbon layer is coated by spray granulation, which specifically includes the following steps:
[0129] In an inert environment without water or oxygen, 2 g of silicon dioxide powder and 0.02 g of lithium metal ingot were weighed and placed in a zirconium oxide ball mill (the weight ratio of lithium metal to silicon dioxide powder was 1:100), and then sealed and transferred to a planetary ball mill for ball milling. The ball-to-material ratio of the ball milling was 20:1, the diameters of the zirconium balls were 5.5 mm, 3.0 mm, and 2.0 mm, and the ratio was 2:5:3. The ball milling speed was 500 rpm, and the ball milling time was 12 hours. 0.5 g of dopamine hydrochloride (the weight ratio of dopamine hydrochloride to lithium metal was 25:1) and 30 g of solvent cyclohexane (the weight ratio of the solvent to dopamine hydrochloride was 60:1) were added, the ball milling speed was 450 rpm, and the ball milling time was 2 hours to obtain a mixed slurry, and the solid content in the mixed slurry was 8.4% by weight. The mixed slurry was spray granulated, with an inlet temperature of 180°C and an outlet temperature of 90°C. Ar gas was used as a carrier gas, with a carrier gas flow rate of 30L / min and a pressure of -0.08MPa to obtain a lithium-containing silicon oxide-based composite material precursor. The lithium-containing silicon oxide material precursor was placed in a tubular furnace under an argon atmosphere for thermal stabilization and two-stage sintering: first, the temperature was raised to 300°C at a rate of 2°C / min, and then kept constant for 2h. After preheating and stabilization, the temperature was raised to 900°C at a rate of 5°C / min, and then kept constant for 2h. After cooling to room temperature, the material was discharged to obtain a pre-lithiation negative electrode material, which was recorded as D-3.
[0130] Example 2
[0131] The difference between this embodiment and embodiment 1 is that the weight ratio of metallic lithium to silicon dioxide powder is changed, and specifically includes the following steps:
[0132] In an inert environment without water or oxygen, 2g of silicon dioxide powder and 0.08g of lithium metal ingot were weighed and placed in a zirconium oxide ball mill (the weight ratio of lithium metal to silicon dioxide powder was 1:25), and then sealed and transferred to a planetary ball mill for ball milling. The ball-to-material ratio of the ball milling was 20:1, the diameters of the zirconium balls were 5.5mm, 3.0mm, and 2.0mm, and the ratio was 2:5:3. The ball milling speed was 500 rpm and the ball milling time was 12 hours. Then 0.1g of natural graphite was added to continue the ball milling (the weight ratio of the solid dispersant to lithium metal was 5:1), the ball milling speed was 450 rpm, and the ball milling time was 2 hours. 0.5 g of dopamine hydrochloride (the weight ratio of dopamine hydrochloride to metallic lithium is 25:1) and 30 g of solvent cyclohexane (the weight ratio of solvent to dopamine hydrochloride is 60:1) were added, the ball milling speed was 450 rpm, and the ball milling time was 2 hours to obtain a mixed slurry with a solid content of 8.9% by weight. The mixed slurry was subjected to spray granulation and two-stage sintering, and the specific conditions were the same as those in Example 1 to prepare a pre-lithiated silicon oxide-based composite material, which was recorded as C-2.
[0133] Example 3
[0134] The difference between this embodiment and embodiment 1 is that the weight ratio of metallic lithium to silicon dioxide powder is changed, and the processing conditions for dispersion and homogenization are changed, which specifically includes the following steps:
[0135] In an inert environment without water or oxygen, 2g of silicon dioxide powder and 0.05g of lithium metal ingot were weighed and placed in a zirconium oxide ball mill (the weight ratio of lithium metal to silicon dioxide powder was 1:40), and then sealed and transferred to a planetary ball mill for ball milling. The ball-to-material ratio of the ball milling was 20:1, the diameters of the zirconium balls were 5.5mm, 3.0mm, and 2.0mm, and the ratio was 2:5:3. The ball milling speed was 500 rpm and the ball milling time was 12 hours. Then 0.25g of natural graphite was added to continue the ball milling (the weight ratio of the solid dispersant to lithium metal was 5:1), the ball milling speed was 250 rpm, and the ball milling time was 5 hours. 1.25 g of dopamine hydrochloride (the weight ratio of dopamine hydrochloride to metallic lithium is 25:1) and 70 g of solvent cyclohexane (the weight ratio of solvent to dopamine hydrochloride is 56:1) were added, the ball milling speed was 450 rpm, and the ball milling time was 2 hours to obtain a mixed slurry with a solid content of 5 wt %. The mixed slurry was subjected to spray granulation and heat stabilization two-stage sintering, and the specific conditions were the same as those in Example 1 to prepare a pre-lithiated silicon oxide-based composite material, which was recorded as C-3.
[0136] Example 4
[0137] The difference between this embodiment and embodiment 1 is that the conditions of the multi-stage sintering process are changed, and the rest of the process is the same as that of embodiment 1, specifically including:
[0138] The lithium-containing silicon oxide material precursor was placed in a tube furnace under an argon atmosphere for thermal stabilization and two-stage sintering: first, the temperature was raised to 500°C at a rate of 3°C / min, then kept constant for 6 hours, and after preheating and stabilization, the temperature was raised to 600°C at a rate of 2°C / min, and then kept constant for 12 hours. After cooling to room temperature, the pre-lithiated silicon oxide-based composite material was obtained, which was recorded as C-4.
[0139] Example 5
[0140] The difference between this embodiment and embodiment 1 is that the amount of the raw materials for the alkali reduction reaction is changed, and the rest of the process is the same as that of embodiment 1, specifically including:
[0141] 0.1 g of dopamine hydrochloride (the weight ratio of dopamine hydrochloride to metallic lithium is 5:1) and 6 g of solvent cyclohexane (the weight ratio of solvent to dopamine hydrochloride is 60:1) were added to prepare a pre-lithiated silicon oxide-based composite material, which was recorded as C-5.
[0142] Example 6
[0143] The difference between this embodiment and embodiment 1 is that the conditions of the spray granulation treatment are changed, and the rest of the process is the same as that of embodiment 1, specifically including:
[0144] The inlet temperature was 300°C, the outlet temperature was 200°C, Ar gas was used as the carrier gas, the carrier gas flow rate was 80 L / min, and the pressure was -0.05 MPa. A pre-lithiated silicon oxide-based composite material was prepared and recorded as C-6.
[0145] Example 7
[0146] In an inert environment without water or oxygen, 2g of silicon dioxide powder and 0.02g of lithium metal ingot were weighed and placed in a zirconium oxide ball mill (the weight ratio of lithium metal to silicon dioxide powder was 1:100), and then sealed and transferred to a planetary ball mill for ball milling. The ball-to-material ratio of the ball milling was 20:1, the diameters of the zirconium balls were 5.5mm, 3.0mm, and 2.0mm, and the ratio was 2:5:3. The ball milling speed was 800 rpm, and the ball milling time was 20 hours. Then 0.2g of mesophase carbon microspheres were added and continued to be ball milled (the weight ratio of the solid dispersant to lithium metal was 20:1), the ball milling speed was 100 rpm, and the ball milling time was 5 hours. Dopamine hydrochloride and organic acid (oxalic acid) were added in a weight ratio of 1:1, a total of 0.5 g (the weight ratio of the raw material for the alkali reduction reaction to metallic lithium was 25:1) and 30 g of solvent cyclohexane (the weight ratio of the solvent to the raw material for the alkali reduction reaction was 60:1), the ball milling speed was 300 rpm, the ball milling time was 3 hours, and a mixed slurry was obtained, and the solid content in the mixed slurry was % by weight. The mixed slurry was spray granulated at an inlet temperature of 240°C and an outlet temperature of 150°C. Ar gas was used as a carrier gas, the carrier gas flow rate was 50 L / min, and the pressure was -0.08 MPa to obtain a lithium-containing silicon oxide-based composite material precursor, and the average particle size of the spray granulation product was μm. The lithium-containing silicon oxide material precursor was placed in a tube furnace under an argon atmosphere for thermal stabilization and two-stage sintering: first, the temperature was raised to 400°C at a rate of 2°C / min, then kept constant for 3 hours, and after preheating and stabilization, the temperature was raised to 800°C at a rate of 5°C / min, and then kept constant for 3 hours. After cooling to room temperature, the pre-lithiated silicon oxide-based composite material was obtained, which was recorded as C-7.
[0147] The component contents, structural parameters and other data of the products obtained in the above examples and comparative examples are listed in the following Table 1.
[0148] Table 1
[0149]
[0150] Test Case
[0151] This test example is used to illustrate the electrochemical performance of the products obtained in the examples and comparative examples when used as negative electrodes of lithium-ion batteries.
[0152] The products obtained in the examples and comparative examples were used as negative electrodes to assemble batteries, and their electrochemical performance was tested. The specific steps are as follows:
[0153] (1) Slurry preparation: weigh the pre-lithiated silicon oxide-based composite material, conductive agent, and binder in a ratio of 8:1:1, add solvent water to adjust the slurry viscosity, and stir for 3 hours.
[0154] (2) Coating: Use a doctor blade to coat the slurry on the copper foil current collector.
[0155] (3) Drying: Dry in a vacuum drying oven at 120°C for 12 h.
[0156] (4) Cutting: Cut the negative electrode into round pieces with a diameter of 15 mm, weigh them and place them in a drying oven.
[0157] (5) Assembly: In a glove box, CR2025 button cells were assembled using lithium sheets as counter electrodes.
[0158] The electrolyte was a 1M LiPF6 / EC:DMC (1:1, vol) mixed solution, and the separator was a Celgard 2300 polypropylene microporous membrane.
[0159] The sealed battery was left to stand for 24 hours, and the battery was subjected to charge and discharge test and cycle performance test using the Land battery performance test system. The test results are shown in Table 2.
[0160] Table 2
[0161]
[0162] According to the data in Table 2 above, we can see that:
[0163] Compared with D-1 to D-3 prepared in comparative examples 1 to 3, the in-situ alkali reduction film-forming pre-lithiation silicon dioxide-based composite material prepared by the method provided in the present invention can obtain higher first coulombic efficiency and cycle capacity retention rate when used as a battery negative electrode.
[0164] The first coulombic efficiency of the battery assembled by directly using conventional silicon oxide without pre-lithiation as the negative electrode material is about 69%, and the capacity retention rate after 100 cycles is about 16%. Compared with silicon oxide as the negative electrode material, the in-situ alkali-reducing film-forming pre-lithiation silicon oxide-based composite material prepared by the method provided in the present invention can be used as the battery negative electrode to obtain a higher first coulombic efficiency and cycle capacity retention rate.
[0165] By comparing Example 1 with Example 2, it can be seen that in the preparation process of Example 2, the weight ratio of metallic lithium to silicon dioxide powder satisfies 1:5-50, the slurry pH of the composite material C-2 prepared in Example 2 is lower than that of C-1 prepared in Example 1, and the first coulombic efficiency and 100 cycle capacity retention rate of C-2 are also higher than those of C-1.
[0166] By comparing Example 1 with Example 3, it can be seen that the weight ratio of metallic lithium to silicon dioxide powder and the dispersion and homogenization processing conditions in Example 3 are all within the optimization range provided by the present disclosure. Compared with the composite material C-1 prepared in Example 1, the composite material C-3 prepared in Example 3 can obtain a higher first coulombic efficiency when used for the battery negative electrode, and has good cycle stability (the cycle capacity retention rate is higher than 100%).
[0167] By comparing Example 1 with Example 4, it can be seen that in Example 1, the composite material is prepared according to the conditions of the multi-stage sintering treatment optimized by the present disclosure. Compared with the composite material C-4 obtained in Example 4, the slurry pH value obtained using the composite material C-1 obtained in Example 1 is smaller and the first coulombic efficiency is higher.
[0168] By comparing Example 1 with Example 5, it can be seen that Example 1 satisfies "the weight ratio of the alkali reduction reaction raw material to metallic lithium is 10 to 30:1" during the preparation process, the slurry pH of the composite material C-1 prepared in Example 1 is lower than that of C-5 prepared in Example 5, the first coulombic efficiency and 100 cycle capacity retention rate of C-1 are also higher than those of C-5, and the addition ratio of dopamine hydrochloride in Example 1 is within the optimized range of the present disclosure, so that the surface of the composite material prepared has a carbon coating layer with a higher film formation degree, which avoids gas production in the slurry.
[0169] By comparing Example 1 with Example 6, it can be seen that in Example 1, the spray granulation treatment is carried out according to the preferred conditions of the present disclosure. Compared with the composite material prepared in Example 6, when the composite material prepared in Example 1 is used for the battery negative electrode, a higher first coulombic efficiency and cycle capacity retention rate can be obtained.
[0170] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0171] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0172] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A pre-lithiated silicon oxide-based composite material with in-situ alkali reduction film formation, characterized in that: The pre-lithiated silicon oxide-based composite material comprises a core-shell structure having a core and an outer shell; The inner core comprises silicon oxide and lithium, and the lithium is selected from one or two of lithium silicate and silicon-lithium alloy; the outer shell is formed by a carbon coating on the surface of the inner core; The carbon coating film is obtained by in-situ reaction of dopamine hydrochloride on the surface of the core.
2. The pre-lithiated silicon oxide-based composite material according to claim 1, characterized in that: The content of the lithium element component in the pre-lithiated silicon oxide-based composite material is 0.01 to 50% by weight, preferably 0.1 to 10% by weight, based on the total amount of lithium element; optionally, the lithium element component also includes metallic lithium; Optionally, the content of the shell is 5 to 50% by weight, preferably 5 to 30% by weight, based on the total weight of the pre-lithiated silicon oxide-based composite material; Preferably, a solid dispersant intermediate layer is further included between the inner core of the pre-lithiated silicon oxide-based composite material and the outer shell.
3. The pre-lithiated silicon oxide-based composite material according to claim 1, characterized in that: The average particle size of the pre-lithiated silicon oxide-based composite material is 0.5 to 50 μm, and the BET specific surface area is 0.1 to 100 m 2 / g, total pore volume is 0.001~0.5cm 3 / g; Optionally, the shell has a thickness of 0.01 to 1 μm, preferably 0.01 to 0.5 μm.
4. A method for preparing a pre-lithiated silicon oxide-based composite material with in-situ alkali reduction film formation, characterized in that: The following steps are involved: S1, contacting metallic lithium with silicon oxide powder and performing solid phase homogenization to obtain a first product; S2, contacting the first product with a solid dispersant and performing a homogeneous dispersion treatment to obtain a second product; S3, contacting the second product with a raw material for alkali reduction reaction and a solvent and performing a mixing and homogenization treatment to obtain a mixed slurry; S4, spray granulating the mixed slurry to obtain a third product; S5, performing heat stabilization treatment on the third product; The above steps S1 to S5 are carried out in an inert atmosphere.
5. The method according to claim 4, characterized in that In step S1, the weight ratio of the metallic lithium to the silicon dioxide powder is 1:1 to 100, preferably 1:5 to 50; Optionally, the metallic lithium is selected from one or more of lithium ingots, lithium wires, lithium powders and lithium sheets; Optionally, the average particle size of the silicon oxide powder is 0.1 to 10 μm, and the BET specific surface area is 0.1 to 100 m 2 / g.
6. The method according to claim 4, characterized in that In step S1, the solid phase homogenization treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser; Optionally, the conditions for the solid phase homogenization treatment include: a ball milling speed of 300 to 2000 r / min, a ball milling time of 6 to 72 h, and a ball-to-material ratio of 1 to 20:1; preferably, the ball milling speed is 500 to 1000 r / min, the ball milling time is 12 to 24 h, and the ball-to-material ratio is 10 to 20:
1.
7. The method according to claim 4, characterized in that In step S2, the weight ratio of the solid dispersant to the metallic lithium is 1 to 50:1, preferably 5 to 10:1; Optionally, the solid dispersant is selected from one or more of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon and soft carbon.
8. The method according to claim 4, characterized in that In step S2, the homogenization and dispersion treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser; Optionally, the conditions for the homogeneous dispersion treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 12 h, and a ball-to-material ratio of 1 to 20:1; preferably, a ball milling speed of 100 to 300 r / min, a ball milling time of 5 to 8 h, and a ball-to-material ratio of 10 to 20:
1.
9. The method according to claim 4, characterized in that In step S3, the weight ratio of the alkali reduction reaction raw material to the metallic lithium is 1 to 50:1, preferably 10 to 30:1; the weight ratio of the solvent to the alkali reduction reaction raw material is 10 to 100:1, preferably 50 to 100:1; Optionally, the solid content of the mixed slurry is 1 to 30% by weight, preferably 5 to 20% by weight; Preferably, the raw materials for the alkalinity reduction reaction include dopamine hydrochloride and an optional organic acid; optionally, the organic acid is selected from one or more of oxalic acid, malic acid and citric acid; Optionally, the solvent is selected from one or more of ethanol, isopropanol, n-butanol, cyclohexane and cyclohexanone.
10. The method according to claim 4, characterized in that In step S3, the mixing and homogenizing treatment includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser; Optionally, the conditions for the mixing homogenization treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 24 h, and a ball-to-material ratio of 1 to 20:1; preferably, a ball milling speed of 100 to 300 r / min, a ball milling time of 0.5 to 3 h, and a ball-to-material ratio of 10 to 20:
1.
11. The method according to claim 4, characterized in that In step S4, the conditions of the spray granulation treatment include: an inlet temperature of 100 to 300°C, an outlet temperature of 50 to 200°C, a carrier gas flow rate of 10 to 100 L / min, and a pressure of -0.10 to -0.05 MPa; Preferably, the inlet temperature is 120 to 240°C, the outlet temperature is 80 to 150°C, the carrier gas flow rate is 30 to 60 L / min, and the pressure is -0.10 to -0.08 MPa; The carrier gas is selected from one or more of argon, nitrogen and helium; Preferably, the average particle size of the third product obtained by spray granulation is 5 to 50 μm.
12. The method according to claim 4, characterized in that In step S5, the thermal stabilization treatment includes a multi-stage sintering treatment; Preferably, the thermal stabilization treatment comprises a first stage sintering treatment and a second stage sintering treatment performed sequentially; The conditions of the first stage sintering treatment include: heating to 200-500°C at a heating rate of 1-3°C / min, and then maintaining the temperature for 1-6 hours; the conditions of the second stage sintering treatment include: heating to 600-1200°C at a heating rate of 2-5°C / min, and then maintaining the temperature for 1-12 hours; Preferably, the conditions for the first sintering treatment include: heating to 250-400°C at a heating rate of 1-2°C / min, and then maintaining the temperature for 2-3 hours; the conditions for the second sintering treatment include: heating to 700-900°C at a heating rate of 3-5°C / min, and then maintaining the temperature for 2-6 hours.
13. A pre-lithiated silicon oxide-based composite material with in-situ alkali reduction film formation prepared by the method according to any one of claims 4 to 12.
14. A negative electrode of a lithium-containing battery, characterized in that: A pre-lithiated silicon dioxide-based composite material for in-situ alkali reduction film formation comprising any one of claims 1 to 3 and claim 13.
15. A lithium-containing battery, characterized in that: Comprising the negative electrode as claimed in claim 14.
